Intraoperative Fluid Management in Patients Undergoing Spine Surgery: A Narrative Review - Ongaigui, Corinna; Fiorda-Diaz, Juan; Dada, Olufunke; Mavarez-Martinez, Ana; Echeverria-Villalobos, Marco; Bergese, Sergio D. (Frontiers in Surgery, 2020)
Fluid management has been widely recognized as an important component of the perioperative care in patients undergoing major procedures including spine surgeries. Patient- and surgery-related factors such as age, length of the surgery, massive intraoperative blood loss, and prone positioning, may impact the intraoperative administration of fluids. In addition, the type and volume of fluid administered may also affect postoperative outcomes. Published literature describing intraoperative fluid management in patients undergoing major spine surgeries is limited and remains controversial. Therefore, we reviewed current literature on intraoperative fluid management and its association with postoperative complications in spine surgery.